Usefulness of a dopamine transporter PET ligand [18F]β-CFT in assessing disability in Parkinson's disease. Issue 6 (1st December 1999) - Rinne, Juha O; Ruottinen, Hanna; Bergman, Jörgen; Haaparanta, Merja; Sonninen, Pirkko; Solin, Olof
Abstract : OBJECTIVES: The usefulness of a novel dopamine transporter PET ligand, [ 18 F]β-CFT in assessing disability in Parkinson's disease was studied. METHODS: Twenty seven patients with Parkinson's disease in different disability stages (of which nine were patients with early disease) and nine healthy controls were studied. The regions of interest were drawn on a magnetic resonance image resliced according to the PET image. RESULTS: There was a significant reduction in [ 18 F]β-CFT uptake in the posterior putamen (to 18% of the control mean, p<0.00001), anterior putamen (28%, p<0.00001), and caudate nucleus (51%, p<0.00001) in the total population of patients with Parkinson's disease. The reduction in [ 18 F]β-CFT uptake was more pronounced with more severe disability of the patients, the correlations between the total motor score of the unified Parkinson's disease rating scale (UPDRS) and [ 18 F]β-CFT uptake being significant in the posterior putamen ( r =−0.62 p=0.0005), anterior putamen (r=-0.64, p=0.0003), and the caudate nucleus ( r =−0.62, p=0.0006). There was a significant negative correlation with putaminal [ 18 F]β-CFT uptake and the hypokinesia and rigidity scores, but not with the tremor score of the UPDRS motor part. In nine patients with early disease and without any antiparkinsonian medication the reduction in the [ 18 F]β-CFT uptake (average of ipsilateral and contralateral side) was reduced in the total putamen to 34% of the mean control value (p<0.00001). The corresponding figures in the other brain areas were: posterior putamen 21% (p<0.00001), anterior putamen 43% (p<0.00001), and caudate nucleus 76% (p<0.01). The reductions in [ 18 F]β-CFT uptake were more severe in the contralateral than in the ipsilateral side. Individually, [ 18 F]β-CFT uptake in the putamen in all patients was below 3 SD from the control mean. CONCLUSIONS: [ 18 F]β-CFT is a sensitive marker of nigrostriatal dopaminergic dysfunction in Parkinson's disease and can be used in the diagnosis, assessment of disease severity, and follow up of patients.